EFFECT OF SOLAR RADIATION ON THE FORMATION OF DISSOLVED GASEOUS MERCURY IN TEMPERATE LAKES - Amyot M.; Mierle G.; Lean D.; McQueen D.J. (My University, 1997)
We have assessed the effect of solar radiation on the formation of dissolved gaseous mercury (DGM) in lake water samples incubated in situ. In temperate forested lakes, solar radiation induced the formation of DGM, whereas in Lake Erie, light had no effect. In lakes where photo-induced DGM production was found, DGM concentrations were higher near the surface, whereas in Lake Erie, DGM levels peaked in the metalimnion. In high DOC lakes, removal of UVB radiation did not affect DGM production, whereas in a low DOC lake, DGM production rates were significantly lower in the absence of UVB radiation, suggesting that DOC compounds are reducing the availability of UVB radiation for photoreduction of Hg. The relationship between light intensity and DGM production was nonlinear in Ranger Lake. Above ~3 MJ m-2 total incident radiation, a plateau was reached at about 400 fM during the summer and about 150 fM during the fall. In this lake, a clear diel pattern of DGM levels was found which paralleled that for total solar radiation. Spiking of samples with Hg(II) prior to incubation in Ranger Lake greatly increased the DGM production rate, suggesting that photoreducible Hg(II) complexes were limiting DGM production. Filtration through GF/F filters or sterilization by heating prior to incubation did not decrease DGM production rates, suggesting that agents promoting DGM formation in Ranger Lake were either dissolved or colloidal. DGM levels in outflows of two high DOC drainage lakes were higher than in inflows, confirming that the lakes were sites of DGM production.